Polyhalites (Polysulphates): Best Soil Ameliorant for Cassava (Manihot esculenta Crantz) in the Ultisols and Entisols of Kerala - K. Susan John; S.K. Bansal; Sanket J. More; G. Suja (JOURNAL OF ROOT CROPS, 2022)
Among the tropical tuber crops, cassava is important due to its higher biological efficiency, larger area under cultivation both for edible and industrial uses, ability to withstand biotic and abiotic stresses, quality starch in the preparation of many value added products including ethanol and biodegradable plastics. In India, cassava is cultivated mainly in Kerala, Tamil Nadu, Andhra Pradesh, Maharashtra and North Eastern States. In Kerala, it is grown as an edible crop and more than 90% of the soils under cassava are acidic (Ultisols), deficient in nutrients like K, Ca, Mg and B. Polysulphate, a natural mineral product containing 18.5% S,13.5% K2O, 5.5% MgO and 16.5% CaO was evaluated in agroecological unit (AEU) 3, AEU 8 and AEU 9 in Kerala for two seasons in five farmers’ fields and one at on station since June 2018 to explore its possibility as a good soil amendment by studying its effect on tuber yield, tuber quality and soil physico-chemical properties. Polysulphate application can be done either as half lime and half dolomite as per lime requirement along with 1-2 t ha-1 polysulphate which resulted in a tuber yield of 53.33 t ha-1 on par with full dolomite along with polysulphate (50.32 t ha- 1) and polysulphate alone (49.24 t ha-1).The yield increase with polysulphate application over PoP, and lime together with dolomite was to the tune of 17.10% and 15.55% respectively. Polysulphate improved bulking of tubers in good form with better quality in terms of cooking, improvement of starch and lowering of bitterness. Though there is no substantial improvement in soil pH, the exchangeable soil K, Ca, Mg and S showed an increase of 80.93, 91, 2.54 and 59.84% over initial compared to 17.84, 90, -11, -0.66% under PoP and 42.39, 82, 18.95 and -3.28% under lime along with dolomite respectively for these nutrients.